1999
DOI: 10.1109/36.739092
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid experimental/theoretical scattering model for dense random media

Abstract: Abstract-The subject of scattering of electromagnetic waves by dense media has been one of intense interest in recent years. The present paper describes polarimetric backscatter measurements made at Ku-band on layers of a dense medium under very carefully controlled circumstances. The experiments have a dual purpose: 1) to evaluate the degree to which the experimental observations are predicted by theoretical, particle-based, random media models and 2) to test a proposed hybrid model by which the scattering an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Other studies have suggested that dry snowpacks are not fully transparent at C-band. A study using artificial snow in a laboratory setting showed a cross-polarized (orthogonal transmitting and receiving antennas) backscatter increase of 5 dB with a 1 m snow depth increase (Kendra, 1995). Two recent tower-based studies showed 2-5 dB increases in co-polarized backscatter for C-band radiation (Naderpour et al, 2022) and significant volume scattering from C-band cross-polarized backscatter at snowpack layering interfaces (Brangers et al, 2023), likely due to surface roughness effects.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have suggested that dry snowpacks are not fully transparent at C-band. A study using artificial snow in a laboratory setting showed a cross-polarized (orthogonal transmitting and receiving antennas) backscatter increase of 5 dB with a 1 m snow depth increase (Kendra, 1995). Two recent tower-based studies showed 2-5 dB increases in co-polarized backscatter for C-band radiation (Naderpour et al, 2022) and significant volume scattering from C-band cross-polarized backscatter at snowpack layering interfaces (Brangers et al, 2023), likely due to surface roughness effects.…”
Section: Introductionmentioning
confidence: 99%